Examination Anxiety Among in-School Adolescents: Parental Factors, School Environment and Gender as Determinants - Habeeb Omoponle Adewuyi; Moromoke Nimota Raji; Babatunde Adewole Ajani; Sylvester E. Umanhonlen; Ayodeji Solomon Adegoke (Indonesian Gender and Society Journal, 2024)
This study examined examination anxiety among secondary school students. The study considers parental factors, school environment, and gender as determinants. This study employed a multi-stage sampling technique. Two hundred and eighty-five secondary school students made the study’s sample. Data was collected using reliable instruments: (Parental Factors scale α = 0.76; School Environment Inventory α = 0.78; and Westside Test Anxiety Scale α = 0.84). From the results, the examination anxiety among students was influenced by gender: females (Mean = 40.5205) and males (Mean = 42.4748). There is a strong correlation between parental factors (r = .688; p.<05), school environment (r = .166; p.<05), gender (r = .081; p.<05) and examination anxiety of students. The most significant contribution to the prediction in terms of magnitude was made by parental factors (β = .680; t = 15.976; p<0.05), followed by School environment (β = .113; t = 2.660; p<0.05) and gender (β = .085; t = 2.013; p<0.05). The study underscores the need for both the home and the school to cooperate to keep the learners focused on their education. They should also encourage, inspire, and equip the students with adequate motivation to reduce anxiety during examinations.